Evaluation of Air Sterility and Biological Safety Cabinets in a Stem Cell Laboratory - Dian Maharsi, Eri; Djannatun, Titiek; Riski, Anika; Adityaningsari, Pratami; Irmawati Purbo Astuti, Ike Irmawati Purbo Astuti (Syntax Literate, 2026)
Stem cell culture requires a highly controlled and sterile environment to ensure cell viability and patient safety. This study aimed to evaluate the microbial contamination levels in the air and the sterility of Biological Safety Cabinets (BSCs) at the YARSI University Stem Cell Laboratory, with the goal of providing recommendations for continuous quality improvement. We used a descriptive quantitative observational approach, collecting air samples from 10 points and two BSCs using a MAS-100 air sampler. Samples were cultured, and the number of Colony Forming Units (CFU) was counted and analyzed against national standards. The results showed a clear distinction between the two environments. Both BSC units demonstrated an sterility level of 0 CFU/m³, confirming the effectiveness of their HEPA filtration. In contrast, the general laboratory area exhibited a varied microbial load, with some areas indicating a need for improved environmental control relative to recommended standards. The identified microorganisms included Candida famata, which is often associated with human flora, and Pseudomonas oryzihabitans, an environmental bacterium. These findings suggest that while BSCs are highly effective barriers, the general lab environment and certain operational practices present areas requiring stricter environmental control. Therefore, infrastructure improvements, such as the installation of an Air Handling Unit (AHU), and the enforcement of stricter Standard Operating Procedures (SOPs) are recommended to maintain overall lab integrity.